Mechanisms of Cardiometabolic Health Outcomes and Disparities: What Characteristics of Chronic Stressors are Linked to HPA-Axis Dysregulation?. (June 2022) - Allen, Julie Ober; Mezuk, Briana; Byrd, DeAnnah R.; Abelson, James L.; Rafferty, Jane; Abelson, Jamie; White, Christopher; Jackson, James S.
Objectives: Chronic stressors are associated with cardiometabolic health conditions and disparities. Mechanisms linking stressors and health remain poorly understood.Methods: Two cohort studies (Cardiac Rehabilitation And The Experience [CREATE] and Tracking Risk Identification for Adult Diabetes [TRIAD]) with harmonized variables were used to examine relationships between six types of chronic stressors in adulthood and Hypothalamic–Pituitary–Adrenal (HPA) axis dysregulation, as indicated by blunted diurnal cortisol slopes, which are stress-sensitive biomarkers implicated in cardiometabolic health (merged N = 213, mean age 61, 18% Black). A secondary aim was to explore whether these chronic stressors accounted for Black–White disparities in HPA axis regulation.Results: Some chronic stressors were linked to HPA axis dysregulation, with recent stressors most salient ( b = 0.00353, SE = 0.00133, p = .008). Black–White disparities in HPA axis regulation persisted after controlling for racial differences in chronic stressors, which reduced the disparity 11.46%.Discussion: Chronic stressors in adulthood may increase risk for HPA axis dysregulation and associated cardiometabolic health outcomes but may not be a key factor in racial disparities.